2016
DOI: 10.1007/978-3-319-43139-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Endometrial Carcinoma: Etiologic Importance of Hormonal and Metabolic Influences

Abstract: Endometrial carcinoma is the most common gynecologic cancer in developed nations, and the annual incidence is projected to increase, secondary to the high prevalence of obesity, a strong endometrial carcinoma risk factor. Although endometrial carcinomas are etiologically, biologically, and clinically diverse, hormonal and metabolic mechanisms are particularly strongly implicated in the pathogenesis of endometrioid carcinoma, the numerically predominant subtype. The centrality of hormonal and metabolic disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 314 publications
0
54
1
2
Order By: Relevance
“…While some risk factors including older age, increasing BMI, and smoking (protective), were associated with EC as expected, the established strong protective risk factor OC use was not significantly associated with reduced risk of EC in our study cohort, but instead showed an increased odds ratio. While the association between OC use and EC is strong and undisputed [11,12], approximately 70% of women in our study, including those with a pathologically unremarkable appearing endometrium, reported past OC use compared with 40e50% of women in other population-based cohort studies [29e31]. Thus, the lack of an association between past OC use and EC in our study is likely secondary to higher OC use in our reference group compared to the general population.…”
Section: Discussioncontrasting
confidence: 65%
“…While some risk factors including older age, increasing BMI, and smoking (protective), were associated with EC as expected, the established strong protective risk factor OC use was not significantly associated with reduced risk of EC in our study cohort, but instead showed an increased odds ratio. While the association between OC use and EC is strong and undisputed [11,12], approximately 70% of women in our study, including those with a pathologically unremarkable appearing endometrium, reported past OC use compared with 40e50% of women in other population-based cohort studies [29e31]. Thus, the lack of an association between past OC use and EC in our study is likely secondary to higher OC use in our reference group compared to the general population.…”
Section: Discussioncontrasting
confidence: 65%
“…Endometrial carcinoma is the most common gynecologic cancer in developed countries (11) and ovarian cancer is the fifth frequent tumor in women (12). Clear cell carcinoma is an uncommon subtype of malignant epithelial tumors in ovary and endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these genes and the transcription factor binding regions in which the five described haplotypes are found have been associated with estrogen-dependent cancers, especially breast cancer. Endometrioid EC is also estrogen-dependent, and the environmental factors associated with this disease are strongly linked to estrogen excess (158)(159)(160), which could explain the increased susceptibility for EC among these haplotypes. Neither potential estrogen excess nor other environmental risk factors for EC have been investigated among the patients and controls in this particular study, which is a weakness of the study design.…”
Section: Study IVmentioning
confidence: 99%